2020
DOI: 10.1002/jctb.6463
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image, Volume 95, Issue 6

Abstract: The cover image is based on the Original Article Dual‐Functionalized Protic Ionic Liquids for Efficient Absorption of NH3 through Synergistically Physicochemical Interaction by Shaojuan Zeng, Yingliang Yang, Lei Yuan et al., https://doi.org/10.1002/jctb.6381.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In their investigation, 1% catalyst mass and 20:1 alcohol:oil molar ratio were employed in which 80% yield was obtained after 6 h of reaction at 100 °C. Yuan et al [32] developed acid-based carbon catalysts which are utilized in the transesterification of soybean oil. In this research, an 8:1 molar ratio of ethanol to oil, 7% of catalyst, and a reaction period of 8 h at 80 °C were employed.…”
Section: Resultsmentioning
confidence: 99%
“…In their investigation, 1% catalyst mass and 20:1 alcohol:oil molar ratio were employed in which 80% yield was obtained after 6 h of reaction at 100 °C. Yuan et al [32] developed acid-based carbon catalysts which are utilized in the transesterification of soybean oil. In this research, an 8:1 molar ratio of ethanol to oil, 7% of catalyst, and a reaction period of 8 h at 80 °C were employed.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the hydrogen bonding interactions between the ionic liquids (ILs) and NH 3 were the key to the signicant increase in NH 3 capacity according to Palomar's work. 23 Therefore, protic ILs 24,25 and ILs substituted with hydroxyl groups, 23,26 and poly ionic liquids (PILs) served as adsorbents of ammonia. 27,28 In our previous work, 29,30 amidine and pyridine-based protic ILs constructed with CHBs presented sigmodal isotherms, and the results indicated a high NH 3 capacity of 7.5-9.3 mmol g −1 at 1 bar, 30 °C; furthermore, the threshold pressure could be regulated through the CHBs.…”
Section: Introductionmentioning
confidence: 99%